2007
DOI: 10.1366/000370207781269738
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Total Internal Reflection Infrared Microscopy of Multilayer Plastic Packaging Foils

Abstract: Multilayer plastic foils are important packaging materials that are used to extend the shelf life of food products and drinks. Fourier transform infrared (FT-IR) spectroscopic imaging using attenuated total internal reflection (ATR) can be used for the identification and localization of different layers in multilayer foils. A new type of ATR crystal was used in combination with a linear array detector through which large sample areas (400 x 400 microm(2)) could be imaged with a pixel size of 1.6 microm. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…It is a powerful technique to find out the spatial distribution of chemical identities within a sample, because we can get full spectral information at each pixel of the obtained IR images. In other words, we can get spatial and chemical information at the same time …”
Section: Surface Morphology Of Pedot‐coated Yarnsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a powerful technique to find out the spatial distribution of chemical identities within a sample, because we can get full spectral information at each pixel of the obtained IR images. In other words, we can get spatial and chemical information at the same time …”
Section: Surface Morphology Of Pedot‐coated Yarnsmentioning
confidence: 99%
“…All the reaction steps, after the oxidant enrichment, were performed as we did in our previous article. [21] For evaluating the effects of drying time and drying temperature, the viscose fibers were first soaked with oxidant (FeCl 3 ) solution and then dried at different temperature (30,40,50, and 60 0 C) for variable times (3, 5, 7, and 10 min). The oxidant concentration, dipping time, and polymerization time were kept constant followed by the other polymerization process as discussed before.…”
Section: Ocvd Polymerization Of Pedotmentioning
confidence: 99%
See 1 more Smart Citation
“…FTIR mapping allows transient effects to be studied in real-time, and the main disadvantage of this technique is the expense of the equipment. ATR mapping can be used to observe the microstructures of mixed polymers and has been used for multilayer packaging films and polymer blends and it has good potential as a technique for studying coarse phase structure in recycled polymer blends [97][98][99].…”
Section: Ftirmentioning
confidence: 99%
“…For example, in a study Arnold J.C. and co-workers used FTIR to investigate some virgin blended and recycled polymers (ABS, HIPS, and PC). The method was compared to optical microscopy and it was reported that the optical microscopy showed up phase separation on a scale of tens of microns, while the FTIR mapping allowed compositional details to be investigated [98]. In another study, FTIR was used to examine plastic plaque samples of television (black plastics) and computer (grey plastics).…”
Section: Ftirmentioning
confidence: 99%